The Effect of Composite Pig Islet-Human Endothelial Cell Grafts on the Instant Blood-Mediated Inflammatory Reaction - Hyoung-Il Kim; Jae Eun Yu; Song Yi Lee; A. Young Sul; Min Seok Jang; M. A. Rashid; Sang Gyu Park; Sang Jun Kim; Chung-Gyu Park; Jae Hyeon Kim M.D., Ph.D.; Kyong Soo Park M.D., Ph.D. (Cell Transplantation, 2009)
Instant blood-mediated inflammatory reaction (IBMIR) causes rapid islet loss in portal vein islet transplantation. Endothelial cells are known to protect against complement-mediated lysis and activation of coagulation. We tested composite pig islet–human endothelial cell grafts as a strategy to overcome IBMIR. Porcine islets were cocultured with human endothelial cells in specially modified culture medium composed of M199 and M200 for 1–9 days. A positive control group, negative control group, and the endothelial cell-coated group were examined with an in vitro tubing loop assay using human blood. The endothelial cell-coated group was subdivided and analyzed by degree of surface coverage by endothelial cells (≤50% vs. >50%) or coculture time (<5 days vs. ≥ 5 days). Platelet consumption and complement and coagulation activation were assessed by platelet count, C3a, and thrombin–antithrombin complex (TAT), respectively. After 60-min incubation in human blood, the endothelial cell-coated group showed platelet consumption inhibition and low C3a and TAT assay results compared to uncoated controls. When the endothelial cell-coated group was subdivided by degree of surface coverage, the ≤50% coated group showed less platelet consumption and less activation of complement and coagulation compared with the positive control (uncoated) group. On analysis by coculture time, only the subgroup cocultured for <5 days showed the same protective effect. Human endothelial cell-coated pig islets, especially the partially coated and short-term cocultured pig islet–human endothelial cell composites, reduced all components of IBMIR. If the optimal endothelial cell–islet coculture method could be identified, human endothelial cell coating of pig islets would offer new strategies to improve xenogenic islet transplantation outcomes.